2004
DOI: 10.1638/03-047
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Evaluation for Ivermectin in Llamas (Lama Glama) After Standard Subcutaneous Dosing

Abstract: Plasma levels of the parasiticide ivermectin were studied by high-performance liquid chromatography in five llamas (Lama glama) after single 200 microg/kg s.c. injections. Ivermectin levels were undetectable in plasma samples drawn up to 4 wk after injection, suggesting that the dosage used was insufficient to reach therapeutic concentrations in this species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…It was suggested that ivermectin binds to ingesta and that this influences the systemic availability of ivermectin after oral administration, however, ATPbinding cassette (ABC)-transporters in the gut might well account for reduced bioavailability. Burkholder et al (2004) found maximum plasma levels after SC injection of ivermectin in llamas to be about one-tenth of those reported in cattle or sheep after SC administration of 0.2 mg/kg BW. Such low drug levels might have significant implications on the development of anthelmintic resistance.…”
Section: Treatment Optionsmentioning
confidence: 68%
See 1 more Smart Citation
“…It was suggested that ivermectin binds to ingesta and that this influences the systemic availability of ivermectin after oral administration, however, ATPbinding cassette (ABC)-transporters in the gut might well account for reduced bioavailability. Burkholder et al (2004) found maximum plasma levels after SC injection of ivermectin in llamas to be about one-tenth of those reported in cattle or sheep after SC administration of 0.2 mg/kg BW. Such low drug levels might have significant implications on the development of anthelmintic resistance.…”
Section: Treatment Optionsmentioning
confidence: 68%
“…Several studies on the pharmacokinetics of ivermectin for the treatment of GINs following subcutaneous (SC) (0.2 mg/kg bodyweight [BW]) or topical (0.5 mg/kg BW) administration to llamas and camels have shown low maximum blood concentrations (<2-4 ng/mL) (Oukessou et al, 1996;Jarvinen et al, 2002;Burkholder et al, 2004). Oral administration (0.2 mg/kg BW) did not lead to detectable plasma levels (Jarvinen et al, 2002).…”
Section: Treatment Optionsmentioning
confidence: 99%
“…5,6,13,14,31,32,34,37,42,[74][75][76][77][78][79][80][81][82][83][84][85] Pharmacokinetic data must be interpreted in the context of evaluating therapeutic concentrations, which depend on the type of drug and the purpose of the drug. Generalizations of the relationship between the pharmacokinetics and pharmacodynamics of antimicrobials were discussed in a previous section, and relatively good data on how to make decisions with a combination of pharmacokinetic, pharmacodynamic, and in vitro antimicrobial susceptibility data are available.…”
Section: Evidence Levelmentioning
confidence: 99%
“…Rotation of anthelmintics must be discour aged, as this practice promotes creation of multiresistant worms. 22 Another study measured the plasma concentrations of iver mectin after dosing llamas by various routes: injectable (0.2 mg/kg subcutaneously), a pouron preparation for cattle (0.5 mg/kg applied on the back after parting the fiber to get to skin), and a paste formulation for horses (0.2 mg/kg orally). This approach takes advantage of the synergism that may occur between anthel mintic classes.…”
Section: Anthelmintic Use For Control Of Haemonchus Contortusmentioning
confidence: 99%